Synthesis, Characterization, and Anticancer Activity of New Metal Complexes Derived from 2-Hydroxy-3-(hydroxyimino)-4-oxopentan-2-ylidene)benzohydrazide - Abdou Saad El-Tabl; Moshira Mohamed Abd El-Waheed; Mohammed Ahmed Wahba; Nahla Abd El-Halim Abou El-Fadl (Bioinorganic Chemistry and Applications)
Novel metal(II) complexes derived from 2-hydroxy-N′-((Z)-3-(hydroxyimino)-4-oxopentan-2-ylidene)benzohydrazide ligand (H2L) were synthesized and characterized by elemental and thermal analyses (DTA and TGA), IR, UV-VIS, 1H-NMR, ESR and mass spectroscopy, magnetic susceptibilities, and conductivities measurements. The complexes adopt distorted octahedral geometry. The ESR spectra of the solid copper(II) complexes are characteristic to d9 configuration and have an axial symmetry type of a d(x2-y2) ground state. The g values confirmed the tetragonal octahedral geometry with a considerably ionic or covalent environment. The cytotoxic activity of the ligand and its metal complexes showed potent cytotoxicity effect against growth of human liver cancer HepG2 cell lines compared to the clinically used Sorafenib (Nexavar).